Review of Anapolisia Piza, 1980 and Tropicophyllum Koçak & Kemal, 2008 stat. rev. (Orthoptera: Tettigoniidae: Phaneropterinae: Microcentrini) - Mendes, Diego Matheus De Mello; Rafael, José Albertino (Zootaxa, 2025)
Anapolisia Piza, 1980 is placed in Microcentrini Brunner von Wattenwyl, 1878 (Orthoptera, Tettigoniidae, Phaneropterinae) and currently comprises six species with distribution from Costa Rica to southern Brazil. In this work, the review of Anapolisia is provided, with a description of 19 new species and Anapolisia planiceps (Walker, 1869) nov. comb. was transferred from Ischyra Brunner von Wattenwyl, 1878; the revalidation of Tropicophyllum Koçak & Kemal, 2008 stat. rev., with a description of 12 new species and new combinations for four species: Tropicophyllum colosseum (Brunner von Wattenwyl, 1878) comb. nov., Tropicophyllum maculosum (Bowen-Jones, 2000) comb. nov., Tropicophyllum sentum (Grant, 1958) comb. nov. and Tropicophyllum zonatum (Giglio-Tos, 1898) comb. nov. Pictorial keys for species, maps and observations of natural history are provided.